Heterogeneous Strategies to Eliminate Intracellular Bacterial Pathogens - Liu, Yuan; Jia, Yuqian; Yang, Kangni; Wang, Zhiqiang (Frontiers in Microbiology, 2020)
Antibiotic tolerance in bacterial pathogens that are genetically susceptible but phenotypically tolerant to treatment represents a growing crisis for public health. In particular, the intracellular bacteria by acting as “Trojan horses” mediated antibiotic tolerance plays a critical and underappreciated role in the disease burden of bacterial infections. How to tackle this problem and therefore deserves more intensified efforts? In this review, we firstly provide a brief overview of modes of action of bacteria invasion and survival in macrophage or non-professional phagocytic cells. Furthermore, we summarize our current knowledge about promising strategies to eliminate these intracellular bacterial pathogens, including direct bactericidal agents, antibiotic delivery to infection sites by various carriers and activation of host immune functions. Finally, we succinctly discuss the faced challenges in bringing them into clinical trials and our constructive perspectives.